ANALISIS PERBANDINGAN MODEL PREDIKSI FINANCIAL DISTRESS ALTMAN DAN SPRINGTE SERTA ZMIJEWSKI (STUDI KASUS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - IKA MAWAR MEIDINA; DJOKO SETYADI; ISNA YUNINGSIH (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
A financial statement analysis its very important for the go public company, financial statement became the company performance report for investor, creditor, suppliers and employee that because they are who will be the most disadvantage if the company have a loss or the worst bankrupt The bankruptcy. Analysis its need to be done, with consideration the bankruptcy a go public company will detrimental to many parties. The object of this research is Banking Companies listed in BEI. The purpose of this research is to know the financial performance and bankruptcy prediction at last five years. The analysis methods in this research is finacial statement ratio analysis and bankruptcy analysis Altman Z-Score model, Zmijewski model and Springate model. The conclusion from the research is financial performance of Bank listed on BEI at years 2010 - 2014 an according to the model Altman Z-Score and Springate all companies that became the object of research is not experiencing financial difficulty or potentially bankrupt, but according to the companies overall Zmijewski model experiencing potential bankcruptcy or in financial difficulty.Keyword :  Bankruptcy, Financial Performance, Financial Rasio, Altman Z-Score, Zmijewski, Springate